2012
DOI: 10.2340/00015555-1246
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pruritus Intensity: Prospective Study on Validity and Reliability of the Visual Analogue Scale, Numerical Rating Scale and Verbal Rating Scale in 471 Patients with Chronic Pruritus

Abstract: The most commonly used tool for self-report of pruritus intensity is the visual analogue scale (VAS). Similar tools are the numerical rating scale (NRS) and verbal rating scale (VRS). In the present study, initiated by the International Forum for the Study of Itch assessing reliability of these tools, 471 randomly selected patients with chronic itch (200 males, 271 females, mean age 58.44 years) recorded their pruritus intensity on VAS (100-mm line), NRS (0-10) and VRS (four-point) scales. Re-test reliability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
423
0
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(447 citation statements)
references
References 39 publications
7
423
0
17
Order By: Relevance
“…However, because VAS rates itchiness in increments along a 100-mm line and NRS uses integers from 0 to 10 to indicate the degree of itchiness, problems such as "the degree of itchiness is difficult to accurately express because the standard is vague," "it is impossible to assess multiple aspects of itchiness with a single number," and "the score is influenced by the symptoms of itchiness and the patient's emotional state immediately before taking the test" have been reported [11,15]. VRS, in which patients express the degree of itchiness by selecting words, has received the following criticism: "There are too few categories with which the patient is required to express minute changes in itchiness, and the differences between the categories are unclear, which results in quantitative inaccuracy" [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because VAS rates itchiness in increments along a 100-mm line and NRS uses integers from 0 to 10 to indicate the degree of itchiness, problems such as "the degree of itchiness is difficult to accurately express because the standard is vague," "it is impossible to assess multiple aspects of itchiness with a single number," and "the score is influenced by the symptoms of itchiness and the patient's emotional state immediately before taking the test" have been reported [11,15]. VRS, in which patients express the degree of itchiness by selecting words, has received the following criticism: "There are too few categories with which the patient is required to express minute changes in itchiness, and the differences between the categories are unclear, which results in quantitative inaccuracy" [12].…”
Section: Introductionmentioning
confidence: 99%
“…The scales used for assessing itchiness include the visual analog scale (VAS) [9][10][11][12], numerical rating scale (NRS) [10][11][12], and verbal rating scale (VRS) [10][11][12]. VAS and the Shiratori severity score for pruritus (Shiratori score) [13], divided into a type of VRS, and the Kawashima classification [14], a simplified version of the Shiratori score, are commonly used in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…One factor that might influence the reliability of measurements is the type of rating scale used to assess itch intensity. Previous research (3)(4) has documented the retest reliability of different rating scales for assessing chronic itch intensity. However, a retest reliability analysis of rating scales for acute experimental itch, induced using substances such as histamine or cowhage, is currently lacking.…”
mentioning
confidence: 99%
“…21 Pruritus was measured using the Visual Analog Scale that evaluates itch on a scale of 0 (no itch) to 100 mm (worst imaginable itch). 22 Results of the trial showed that the wearable sensor caused little to no irritation (cumulative and mean skin irritation scores: 0-0.1) and mild increase in pruritus (mean change from baseline at all visits: 14.2-18.6 mm). The wearable sensor was well tolerated, with no adverse events reported during the trial.…”
Section: Dermal Safetymentioning
confidence: 95%